2005
DOI: 10.1089/tmj.2005.11.608
|View full text |Cite
|
Sign up to set email alerts
|

Can Subspecialty Cancer Consultations Be Delivered to Communities Using Modern Technology?—A Pilot Study

Abstract: The objective of this project was to evaluate patient and physician acceptance of subspecialty oncologic teleconsultation for distant communities. Many newly diagnosed cancer patients have to travel several hours and long distances to attend specialty medical oncology consultations at our regional cancer center in Victoria, BC. Difficulties in recruiting of oncologists in Vancouver Island have prompted the search for other means to deliver subspecialty consultation closer to home. Teleconsultation seemed a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 10 publications
3
55
0
Order By: Relevance
“…In the later cohort, when our model was operating smoothly, only 2 patients preferred to travel. Results of our survey are not dissimilar to other surveys indicating overall satisfaction with this model of care (Weinerman et al, 2005;Taylor,2007). Major benefits include travel time saved and improved access to specialist services.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…In the later cohort, when our model was operating smoothly, only 2 patients preferred to travel. Results of our survey are not dissimilar to other surveys indicating overall satisfaction with this model of care (Weinerman et al, 2005;Taylor,2007). Major benefits include travel time saved and improved access to specialist services.…”
Section: Discussionsupporting
confidence: 45%
“…A regional cancer centre in Victoria Canada compared satisfaction levels between 60 sequential patients, 30 consulted via videoconferencing, and 30 seen face to face (Weinerman et al;. Results demonstrated patients were very satisfied with teleconsultation, particularly as it saved travel time.…”
Section: Satisfaction Of Patients and Health Care Workers 411 Intromentioning
confidence: 99%
“…In another study relating to subspecialty cancer consultations in the field of gastroenterological oncology, Weinerman and colleagues found that there was no difference in patient satisfaction between video conferencing and face-to-face consultations. 7 However, in this investigation, participating oncologists actually felt that the video media were not as satisfactory as the person-to-person patient interviews.…”
Section: Discussionmentioning
confidence: 76%
“…[6][7][8] Although several reviews of patients' level of satisfaction and overall functionality of teleoncology services have been published, there is relatively little in the literature relating to recipient client physician satisfaction. 9,10 Some have argued that it is difficult to generalize the results from individual telemedicine projects across all types of telemedicine programs.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine has shown such promise in numerous specialties including dermatology, 21 psychiatry, 22 and oncology. 23,24 Data from studies of telemedicine in these specialties show that telemedicine improves access to medical care in underserved communities and patients are as satisfied with receiving medical care via telemedicine as with the same specialty consultations performed in person. [21][22][23][24] Of note, equal satisfaction holds for groups that might not be expected to be comfortable with telemedicine technology, such as the elderly.…”
Section: Introductionmentioning
confidence: 99%